-5(2x-3)=2(x-13)-7

Simple and best practice solution for -5(2x-3)=2(x-13)-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(2x-3)=2(x-13)-7 equation:



-5(2x-3)=2(x-13)-7
We move all terms to the left:
-5(2x-3)-(2(x-13)-7)=0
We multiply parentheses
-10x-(2(x-13)-7)+15=0
We calculate terms in parentheses: -(2(x-13)-7), so:
2(x-13)-7
We multiply parentheses
2x-26-7
We add all the numbers together, and all the variables
2x-33
Back to the equation:
-(2x-33)
We get rid of parentheses
-10x-2x+33+15=0
We add all the numbers together, and all the variables
-12x+48=0
We move all terms containing x to the left, all other terms to the right
-12x=-48
x=-48/-12
x=+4

See similar equations:

| 14=-4+2z | | 2x+5(2x-5)=71 | | 5y/3=2y/3 | | 2+2x=3(-x+4)-20 | | 7x-9=8x-10 | | 5y/3-5/3=2y/3-5/3 | | 7y-9y+1=5 | | 4=k/2=-3 | | 16x-53=12x-37 | | /145=z/25 | | 2x+3-1=-x+8 | | /145=z25 | | 7y-9y=1=5 | | 2x+2=1x+10 | | 19a-98=14a-63 | | -52=4-8u | | 9x+72=4x+122= | | w+36=2w+29 | | 4b-59=2b-17 | | 11.02+0.8v=-0.7v−16.88 | | t=3t-62 | | s=6s-35 | | 9k=11k+14 | | r−15.9=−2.4 | | x=(109.61x+8557.7)-8557.7/109.61 | | 7t-50=10t-86 | | -19-6p=-19p+20 | | 6=-2-2x=10 | | z-10=2z-63 | | 8/3c-2=2/3​c−12 | | 12y-4.75=13.9y | | 4.2+z=-8 |

Equations solver categories